Association of serum Nrf2 protein levels with disease activity and renal impairment in lupus nephritis - Li, Jicui; Guo, Qiaoyan; Wei, Xianping; Zhu, Yuexin; Luo, Manyu; Luo, Ping (Frontiers in Immunology, 2024)
We aimed to investigate the relationship between nuclear factor erythroid 2-related factor 2 (Nrf2) protein expression levels, lupus nephritis (LN) disease activity, and the degree of renal injury (based on the estimated glomerular filtration rate [eGFR]) in patients with LN. Methods: We selected 40 healthy control participants and 102 patients with LN who were treated in the Second Hospital of Jilin University, China, for inclusion in this study. Patients with LN were classified into LN with high-eGFR and LN with low-eGFR groups. Nrf2 protein levels were measured in the serum and renal tissues of the participants in both groups to assess the correlation between Nrf2 protein levels and different LN disease states. Results: There was a significantly positive correlation between serum Nrf2 protein levels, the degree of renal injury, and systemic lupus erythematosus disease activity index (SLEDAI) scores in patients with LN. Nrf2 protein levels were higher in the LN with high-eGFR group than in the healthy control and LN with low-eGFR groups. In follow-up patients in the LN high eGFR group, Nrf2 protein levels decreased significantly after remission of disease activity. Conclusion: Nrf2 protein expression has a dual role in patients with LN. Nrf2 protein levels not only correlate with disease activity in patients with LN, but also with the degree of kidney injury. Before implementing targeted therapy for Nrf2, evaluating both Nrf2 protein expression and the disease state in patients with LN is necessary to better identify and place each patient in an appropriate patient group.